'It depends what you mean by leadership': An analysis of stakeholder perspectives on consumer leadership. (3rd October 2018) - Stewart, Stephanie; Scholz, Brett; Gordon, Sarah; Happell, Brenda
Abstract: Contemporary mental health policies call for increased involvement of consumers in leadership across mental health service design, delivery, and evaluation. However, consumer leadership is not currently well understood within academia or in mental health services themselves. This study investigates how consumer leadership is currently conceptualized by stakeholders at the service delivery level. To this end, semistructured interviews were conducted with 14 mental health organization members identifying as consumer leaders, colleagues supporting consumer leaders, or organization executives. Interview data were analysed using an inductive thematic analysis to develop a broad understanding of participants' perceptions of consumer leadership. Findings indicate constructions of consumer leadership within mental health organizations can be understood in relation to four themes: consumer leadership roles, requirements, purpose, and process. Inconsistencies across participants' perceptions of consumer leadership were identified as constituting barriers to its development, highlighting the need to better clarify the nature of consumer leadership.